Clinical research The effects of L-thyroxin replacement therapy on bone minerals and body composition in hypothyroid children - Salama, Hassan M.; El-Dayem, Soha A.; Yousef, Hala; Fawzy, Ashraf; Abou-Ismail, Laila; El-lebedy, Dalia (Archives of Medical Science, 2010)
Introduction: Prolonged treatment with levothyroxine 4 (L-T4) is a well known risk factor for osteoporosis. Patients on L-T4 replacement occasionally have a subnormal TSH, which carries a risk of development of bone loss. Thyroid hormones directly affect bone cells, stimulating osteoclastic and osteoblastic activity with a predominance of bone resorption and decrease of bone mineral density (BMD). Material and methods: The study included 35 hypothyroid patients with mean age 11.57 ±5.06, while 26 age- and sex-matched children served as controls. Dual energy X-ray absorptiometry (DXA) was done to detect the bone mineral density (BMD), bone mineral content (BMC) and Z score in lumbar and femur neck regions. Body composition was also studied by DXA. Calcium, phosphorus, osteocalcin as a bone formation marker, osteoprotegerin as an indicator of osteoclast activity and urinary deoxypyridinoline as a bone collagen breakdown marker were assessed. Results: No significant differences were detected in lumbar Z score (–0.12 ±0.66) and femur Z score (–0.17 ±0.58) compared to controls (–0.33 ±0.74 and –0.21 ±0.53 respectively). Bone mineral density and BMC were not significantly different from controls. No significant difference was detected between cases and controls in body composition. A positive correlation was detected between BMD and age (r = 0.857, p < 0.01), and with the period of treatment (r = 0.766, p < 0.01). A positive correlation was found between BMD and total body fat (r = 0.693, p < 0.01), and with abdominal fat (r = 0.667, p < 0.01). Conclusions: Levothyroxine 4 treatment in hypothyroid children does not alter bone metabolism and body composition